A comprehensive program for enhanced management of femoral neck fractures including an enhanced recovery after surgery program: A retrospective study. Issue 5 (5th February 2021) - Huang, Zheyu; Zhang, Junhui; Di, Zhenglin; Zeng, Zhimin
Abstract : Abstract: To retrospectively analyze the functional outcomes and complications in patients who underwent hip arthroplasty with enhanced recovery after surgery (ERAS) program for femoral neck fractures. Between June 2015 and May 2019, 1138 patients with femoral neck fractures were treated in our department. According to the Garden classification system, 467 cases were type III and 671 cases were type IV with an average age of 74.9 ± 8.8 years (range, 59–96 years). All patients underwent hip arthroplasty with ERAS. The clinical outcomes of these patients were retrospectively analyzed at the final follow-up using the Harris hip score (HHS). The median follow-up was 21.2 months (range, 6–36 months). The mean time to surgery and the length of hospitalization after surgery were 2.4 and 2.2 days, respectively. Eight hundred and fifty-two patients (74.9%) were operated within 48 hours from admission, 1052 cases (92.4%) were discharged within 48 hours after surgery. Twelve patients (1.05%) were readmitted for prosthetic dislocation. None of the patients suffered from infection, periprosthetic fractures, and/or prosthetic loosening. The HHS at the final follow-up was 92.7 ± 7.6, with an excellent or good rate of 90.2%. Patient-oriented ERAS optimizes the interventional measures during the perioperative period for geriatric patients with femoral neck fractures and can improve their short-term clinical outcomes without increased readmission rates.